2014
DOI: 10.1080/00918369.2014.957133
|View full text |Cite
|
Sign up to set email alerts
|

Outside Looking In: The Community Impacts of Anti-Lesbian, Gay, and Bisexual Hate Crime

Abstract: Hate crime scholars have long argued that the harms of hate crime extend beyond the immediate victim to negatively impact the victim's reference community. However, this assertion is speculative and in need of empirical support. Utilizing focus group data from 15 people who identified as lesbian, gay, bisexual, or pansexual, this pilot study explored the extent to which the harms of anti-LGB hate crime spread beyond the immediate victim to impact nonvictims in the LGB community. The findings suggest that anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
26

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 35 publications
3
62
0
26
Order By: Relevance
“…A recent study by the Sussex Hate Crime Project found that hate crimes against lesbian, gay, bisexual, and transgender (LGBT) people and Muslim people not only traumatized direct victims but also had substantial negative impacts on other members of the victim's group which were similar to those of direct victims (what the authors call "indirect hate crime") (Brown & Walters, 2016). They reported that indirect victimization (in this case, personally knowing other victims of hate crime with similar identity characteristics) was clearly associated with different behavioral intentions (pro-action and avoidance) 1 which were mediated by various emotional reactions (anger, anxiety, and shame; see also Bell & Perry, 2015;Perry & Alvi, 2012). This growing body of work has provided important information on the emotional, behavioral, and spatial impacts of hate crime.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by the Sussex Hate Crime Project found that hate crimes against lesbian, gay, bisexual, and transgender (LGBT) people and Muslim people not only traumatized direct victims but also had substantial negative impacts on other members of the victim's group which were similar to those of direct victims (what the authors call "indirect hate crime") (Brown & Walters, 2016). They reported that indirect victimization (in this case, personally knowing other victims of hate crime with similar identity characteristics) was clearly associated with different behavioral intentions (pro-action and avoidance) 1 which were mediated by various emotional reactions (anger, anxiety, and shame; see also Bell & Perry, 2015;Perry & Alvi, 2012). This growing body of work has provided important information on the emotional, behavioral, and spatial impacts of hate crime.…”
Section: Introductionmentioning
confidence: 99%
“…Hatbrottsutsatthet har dessutom visat ha en negativ inverkan på både direkta och indirekta brottsoffers psykiska och fysiska välbefinnande samt hälsosituation (Bell & Perry, 2015;Lehavot et al, 2011;Lim, 2009;McDevitt, Balboni, Garcia & Gu, 2013;Meyer, 2003;Perry & Alvi, 2011;Roberts et al, 2010). Andersson & Mellgren (2015) har kritiserat att de flesta hatbrottsstudier i allmänhet har varit inriktade på att studera individuella motiv och specifika gruppers konsekvenser av utsatthet och påminner oss om att ett brottsoffer i själva verket kan vara offer för flera olika motiv samtidigt.…”
Section: Utsatthetens Konsekvenserunclassified
“…Dessa brott anses sedan medföra negativa effekter för hela grupper av individer (indirekta brottsoffer) och eventuellt problematisera situationen mellan olika grupper (Perry, 2001). Huruvida sådana brott i realiteten har dessa så kallade "rippel effects" har dock sällan studerats empiriskt (för några exempel på undantag se exempelvis Bell & Perry, 2015;Lim, 2009). Denna aktuella studie ger dock stöd för detta påstående.…”
Section: Diskussion Och Slutsatserunclassified
“…Det handlar om, menar en del forskare, att få hela sin identitet ifrågasatt (Iganski, 2001;McDevitt, Balboni, Garcia & Gu, 2013). Resultat från den forskning som har behandlat hatbrottens konsekvenser visar bland annat att individer som utsätts för hatbrott ofta upplever en lägre nivå av generell säker-het vilket i sin tur har en inverkan på deras livskvalitet (Bell & Perry, 2015;Lehavot et al, 2011;Lim, 2009;McDevitt, Balboni, Garcia & Gu, 2013;Meyer, 2003;Perry & Alvi, 2011;Roberts et al, 2010). I vissa fall kan denna rädsla leda till att brottsoffer isolerar sig eller börjar med att undvika vissa platser och situationer då de upplever en specifik situation som hotfull (Hale, 1996;Ford, 2012).…”
Section: Hur äR Hatbrott Ett Problem?unclassified